Metal-Free sp3 C–H Functionalization: PABS/I2-Promoted Synthesis of Polysubstituted Oxazole Derivatives from Arylethanones and 2-Amino-2-alkyl/arylacetic Acid - Hu, Ting; Yan, Hao; Liu, Xingxing; Wu, Chaoyang; Fan, Yuxing; Huang, Jing; Huang, Guosheng (Synlett, 2015)
A nonmetal-catalyzed process for the synthesis of polysubstituted oxazoles from inexpensive and readily available α-amino acids and methyl ketones is established. This reaction is proposed to achieve oxidative cleavage of C(sp3)–H bonds, followed by decarboxylation and annulation. The mild reaction conditions employed in both cases enable the tolerance of a wide range of functional groups as well as high reaction efficiency.
Keywords: nonmetal-catalyzed; oxazoles; sp3 C–H functionalization; high yield; amino acids